New Publications Of The Bureau Of Mines - List 937 - Jan.- Feb. 1995 - Electronic Information (The National Institute for Occupational Safety and Health (NIOSH), 1995)
Commodities statistics and otter information are available through the following t et systems: Internet Access: To acccess the USBM Gopher server on Internet, connect to: gopher.usbm.gov port 70, using gopher client software. Or contact the Systems Administrator for technical questions: Matt Klevemann, 412-892-6499 (klevemmc@miner.usbm.gov) These USBM materials are available on Internet, with more to come in the future: Publications and other research findings, including this bimonthly publications list, newsletters, tech transfer updates, enviromental technology research, health and safety information. USBM software products Media materials and speeches. Mines Data: Computer bulletin board. Log on via modem through 202/501-0373, or call 202/501-0406 for technical assistance. Mines FaxBack: Return fax service. 1. Use the touch-tone handset attached to your fax machine's telephone jack. (ISDN [digital] telephones cannot be used with fax machines.) 2. Dial 202/219-3644. 3. Listen to the menu options and punch in the number of your selection, using the touch-tone telephone. 4. After completing your selection, press the start button on your fax machine.